Environmental sustainability of green marketing strategy: empirical evidence from e-tail consumer's in Tamil Nadu. (2018) - Annamalai, Suresh; Kumar, K.R.; Jothikumar, R.; Hung, Yung-Tse
Green marketing is one of such strategies used by marketers for reaching sustainable development. Companies need to know consumers' attitude and to adapt new marketing solutions with the focus on determining the expectations and satisfying their needs. In this paper, we will attempt to examine the attitude of Tamil Nadu e-tail consumers toward eco-friendly products. The aim of the survey is to gather information from a consumer standpoint. Time has witnessed the different phases of marketing strategy. Out of which, sustainability is the key issue which has emerged in marketing strategy over the time. In earlier phase of 1970s, ecological issues have emerged as a new paradigm in marketing strategy. Reassessment of the issues resulted in evolution of green or environmental issues in marketing strategy and now the sustainability in marketing strategy has become the focus of attention of the researchers.